Energy-Environmental Analysis of Retrofitting of a Chilled Water Production System in an Industrial Facility—A Case Study - Tomasz Mróz; Kacper Fórmaniak (Applied Sciences, 2025)
This paper presents a method of evaluating energy and environmental factors before and after chilled water production system retrofitting at an industrial facility. A general algorithm was used for the analysis of chilled water system retrofitting at a pharmaceutics factory. Two retrofitting variants based on dual-stage absorption chillers supplied from an existing gas-fueled co-generation plant were identified. The proposed variants, i.e., tri-generation systems, were compared with the basic variant, which relied on electric compression water chillers. An evaluation of the variants was performed on the basis of two criteria: annual primary energy consumption and annual carbon dioxide emission. Variant 2, i.e., with a 1650 kW dual-stage absorption water chiller supplied from an existing gas fueled co-generation plant, was chosen as the optimal variant. It achieved a 370 MWh annual primary energy consumption reduction and a 1140 Mg annual carbon dioxide emission reduction. It was found that increasing the co-generation ratio for the CHP plant powering the pharmaceutical factory resulted in lower consumption of primary energy in variants in which the cooling energy supply system was retrofitted based on absorption water chillers. The threshold values of the co-generation ratio were e = 0.37 for Variant 1 and e = 0.34 for Variant 2. A literature survey revealed that there is limited interest in the application of such a solution in industrial plants. The performed analysis showed that the evaluated systems may nonetheless be an attractive option for pharmaceutics factories, leading to the reduction of primary energy consumption and carbon dioxide emissions, thereby making more electrical power available for core production. The lessons learned during our analysis could be easily transferred to other industrial facilities requiring chilled water production systems.